Reduced risk of dyslipidaemia with oolong tea consumption: a population-based study in southern China. Issue 8 (28th April 2014) - Yi, Deqing; Tan, Xuerui; Zhao, Zhiguo; Cai, Yingmu; Li, Yiming; Lin, Xiuying; Lu, Sailan; Chen, Yongsong; Zhang, Qingying
<x content-type="archive" xml:space="preserve">Abstract</x> Experimental studies have suggested that tea consumption could lower the risk of dyslipidaemia. However, epidemiological evidence is limited, especially in southern China, where oolong tea is the most widely consumed beverage. We conducted a population-based case–control study to evaluate the association between consumption of tea, especially oolong tea, and risk of dyslipidaemia in Shantou, southern China, from 2010 to 2011. Information on tea consumption, lifestyle characteristics and food consumption frequency of 1651 patients with newly diagnosed dyslipidaemia and 1390 controls was obtained using a semi-quantitative questionnaire. Anthropometric variables and serum biochemical indices were determined. Drinking more than 600 ml (2 paos) of green, oolong or black tea daily was found to be associated with the lowest odds of dyslipidaemia risk (P< 0·001) when compared with non-consumption, but only oolong tea consumption was found to be associated with low HDL-cholesterol levels. A dose–response relationship between duration of tea consumption and risk of dyslipidaemia (OR 0·10, 95 % CI 0·06, 0·16), as well as that between amount of dried tea leaves brewed and risk of dyslipidaemia (OR 0·34, 95 % CI 0·24, 0·48), was found. Moreover, consumption of oolong tea for the longest duration was found to be associated with 3·22, 11·99 and 6·69 % lower blood total cholesterol, TAG and LDL-cholesterol levels, respectively. In conclusion, the present study indicates that long-term oolong tea consumption may be associated with a lower risk of dyslipidaemia in the population of Shantou in southern China.